An evaluation of effectiveness of approximate quantity method in estimating construction cost - Siew, Sik Nguong, 1989-; Khairulzan Yahya, supervisor; Fakulti Kejuruteraan Awam (2013)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2013